Enhancing Computational Thinking through a 2D Block-Coding Game: A Comparative GDLT–TAM Study in Elementary Education - Wibowo, Tony; Wilson, Wilson; Gernaldi, Kevin; Simanjuntak, Fredian (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
The aims of this study was to develop and evaluate a 2D block- coding educational game designed to introduce computational thinking concepts to elementary school students. The game was developed using the Game Development Life Cycle Theory (GDLT), while its acceptance was evaluated using the Technology Acceptance Model (TAM), focusing on perceived usefulness, ease of use, attitude, and behavioral intention. The study involved 122 students from grades 3 and 6, divided into two groups: Group A received instructional guidance before gameplay, while Group B played the game without guidance. Data were collected through classroom observations and semi-structured interviews and analyzed using deductive thematic analysis based on the TAM framework. The results showed clear differences between the two groups. Group A demonstrated faster understanding of block- coding concepts, required fewer attempts to complete levels, and exhibited more consistent learning progress. In contrast, Group B experienced a longer adjustment period and relied more on trial- and-error learning. Group A also perceived the game as more useful and easier to use, and showed a stronger intention to continue using it. Overall, the findings indicate that the proposed game is an effective tool for introducing computational thinking in elementary education and highlight the importance of combining instructional guidance with game-based coding to enhance learning effectiveness and user acceptance.